Reflexos da terceirização no serviço público federal : análise de elementos do contrato de serviços de limpeza da Universidade Federal de São Carlos frente à reforma do estado - D’Angelo, Camila Luchesi Silveira (2015)
Outsourcing is a premise of flexible work that emerged on second half of 20th century and was quickly spread around the world. Coming to Brazil, it was included in government's guidelines around 1960's, in order to reduce the state apparatus. During the Reform of Brazilian State, in the 1990's, this form of hiring took larger proportions – although it was not the main theme of the changes – due to the issued legislation, specially for decree no. 2.271 of 1997, which determined that ancillary activities in federal service must be extinguished and substituted by located labor. Since then, an increasing number of administrative contracts have been signed between the public authority and service provider companies. This dissertation considers this context. The case study aims to investigate some of the influences exerted by the legislation created during the last Reform of Brazilian State over the contracts execution, taking as example the last experience of cleaning service at Universidade Federal de São Carlos. The text presents some general outsourcing concepts and history; the reforms by which Brazilian State has gone through during the last century and its consequent chances; the characterization of the institution where the search has been developed; a critical analysis of the cleaning service contract, highlighting the points concerning to supervision, for which, not only a public worker, but a monitoring Commission and a accompaniment group were designated. Finally, a sketch of satisfaction survey is proposed, to be answered by the whole academic community, objecting to reveal the user's view about the studied service. The legal instruments which permit practical contract inspection are often considered onerous and insufficient to avoid damaging denouement to the service, the public authority and, especially, to the employees hired by this work regime.